Edgar Degas - Portrait Of Madame Fontaine - Edgar Degas (NC, 2026)
Edgar Degas Portrait of Madame Fontaine (Clarisse Leontine 1834-1877) from Guignes Rabutin (Seine-et-Marne) . Painted in Paris 1873
Licence indiquee par Wikimedia Commons
Keywords: Degas; Peintures; Musée; musée; musée national